# Solve for t -0.09=(25)(22.2*10^-6)(t-19) -0.09=(25)(22.2⋅10-6)(t-19)
Rewrite the equation as (25)(22.2⋅10-6)(t-19)=-0.09.
(25)(22.2⋅10-6)(t-19)=-0.09
Simplify.
Write 22.2⋅10-6 in proper scientific notation.
25(2.22⋅10-5)(t-19)=-0.09
Group coefficients together and exponents together to multiply numbers in scientific notation.
(25⋅2.22)(10-5)(t-19)=-0.09
Multiply 25 by 2.22.
55.5⋅10-5(t-19)=-0.09
Write 55.5⋅10-5 in proper scientific notation.
5.55⋅10-4(t-19)=-0.09
5.55⋅10-4(t-19)=-0.09
Divide each term by 5.55⋅10-4 and simplify.
Divide each term in 5.55⋅(10-4(t-19))=-0.09 by 5.55⋅10-4.
5.55⋅(10-4(t-19))5.55⋅10-4=-0.095.55⋅10-4
Cancel the common factor of 5.55⋅10-4.
t-19=-0.095.55⋅10-4
Simplify -0.095.55⋅10-4.
Divide using scientific notation.
Group coefficients together and exponents together to divide numbers in scientific notation.
t-19=(-0.095.55)(110-4)
Divide -0.09 by 5.55.
t-19=-0.0162‾110-4
Move 10-4 to the numerator using the negative exponent rule 1b-n=bn.
t-19=-0.0162‾⋅104
t-19=-0.0162‾⋅104
Write -0.0162‾⋅104 in proper scientific notation.
t-19=-1.621‾⋅102
Convert -1.621‾⋅102 from scientific notation.
t-19=-162.162‾
t-19=-162.162‾
t-19=-162.162‾
Move all terms not containing t to the right side of the equation.
Add 19 to both sides of the equation.
t=-162.162‾+19